PEMBELAJARAN MENGIDENTIFIKASI UNSUR TEKS BERITA MENGGUNAKAN MODEL STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) PADA FASE D - Maharani Putri; Rustam; Sophia Rahmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the learning process and results of students' identification of news text elements after participating in learning using the Student Teams Achievement Division (STAD) model. The study used a descriptive qualitative approach with an instrumental case study. Data were obtained through observation, interviews, and documentation. The results indicate that learning using the STAD model proceeded systematically and encouraged student engagement through material presentation, group discussions, and individual assignments. Individual assignment results indicated that students found it easier to identify the elements of what, where, and when, while the elements of who, why, and how demonstrated varying abilities. Overall, the STAD model helped students identify news text elements more accurately.